Penerapan Data Mining pada Program Pembangunan Sarana dan Prasarana Desa Menggunakan Algoritma ID3 - Luvi, Nurindah (Bulletin of Data Science, 2022)
The implementation of village development is one of the agendas that the village government continues to carry out. These development programs are structured to meet the needs of the community and village government institutions. The implementation of development begins with planning and planning through a deliberation forum involving the village government and community institutions. The development program must of course be adapted to the aspirations of the community, needs, and applicable regulations. The purpose of this study is the application of data mining in the village facilities and infrastructure development program with the ID3 algorithm method carried out by the author including field studies, literature studies and interviews. From the analysis and observations made, it can be seen that the application of data mining in village facilities and infrastructure development programs with the ID3 algorithm method is an effective alternative to improve services to work units, so that it is expected to be able to produce information quickly, precisely and accurately with does not detract from the value of the information itself.